¿Right to the city? The city as a place and a possibility for human rights - Correa Montoya, Lucas (Universidad del Rosario, 2011)
The Right to the City as a collective right includes in its definition three necessary aspects: (a) the equitable use and access by all it inhabitants to all advantages offered by the city, (b) the collective participation of its inhabitants in all urban and city matters and (c) the effectiveness of all human rights in the urban context. All citizens, consider in a wide way, are entitle of the Right to the City and the city’s public authority is the responsible for its implementation and guarantee. Nevertheless, owing to the fact of its complex nature, the Right must be based on a system of co-responsibilities to make it a reality.